Acceleration of Siamese Citrus Agro Business through Food Processing Technology and Digital Marketing - Ni Luh Putu Indiani; Ida Bagus Udayana Putra; I Gede Pasek Mangku; Pavalee Chompoorat Tridtitanakiat; Ni Nyoman Trisnayanthi; A. A. Rai Darmawan (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2024)
This article discusses the outcomes of a community service program conducted to accelerate the Siamese citrus agro-business in Pelaga Village, Bali. The initiative focused on addressing key challenges faced by local farmers, including limited post-harvest processing capabilities and a lack of digital marketing knowledge. The program aimed to empower farmers by introducing modern food processing technologies and enhancing their digital marketing skills, thereby improving both the quality and marketability of their products. Over the course of the program, farmers participated in comprehensive training sessions that covered techniques for processing oranges into value-added products such as packaged fruit juice and orange powder. Additionally, the program provided essential equipment and facilitated technology transfer to support these new practices. Digital marketing strategies were also a core component, with farmers receiving guidance on how to effectively utilize social media and e-marketplace platforms to reach a broader customer base. The results of the program were significant, leading to increased income for farmers, reduced post-harvest losses, and expanded market access both locally and internationally. The introduction of these innovations not only enhanced the economic resilience of the farming community but also promoted sustainable agricultural practices. This article presents a detailed account of the program's methodology, the outcomes achieved, and the broader implications for similar agribusiness initiatives. The findings underscore the potential of integrated technological and marketing interventions in driving rural economic development and empowering local communities.